Law Enforcement Against Cosmetic Businesses Operating Without a BPOM Distribution Permit - Inayatun Nazliyah; Fajar Rachmad Dwi Miarsa; Dhofirul Yahya; Ahmad Heru Romadhon (Journal of Law, Politic and Humanities, 2025)
According to applicable law, cosmetics are pharmaceutical products that can only be distributed after obtaining a distribution permit. This permit serves as a consumer protection measure to ensure the safety of cosmetic products. To regulate the circulation of cosmetics without a valid distribution permit, the government has established regulations to oversee their distribution, ensuring consumer protection. This study aims to examine the legal framework governing cosmetic business licenses and the legal responsibilities of cosmetic business operators who lack a distribution permit. The research employs a normative juridical approach. Before being marketed, every cosmetic product must obtain a distribution permit through a notification process with the Food and Drug Supervisory Agency. Cosmetic distributors operating without this permit may face legal consequences, including both criminal and administrative sanctions.